Using Schoology in the Era of IR 4.0 (Factors Analysis From Students’ Perception) - Sriyanto, Widi; Kaniadewi, Nita (Universitas Malikussaleh, 2019)
This study aimed to gain students' perceptions in the use of Schoology to assist their learning activities in the era of industrial revolution 4.0. This study involved four classes that applied online and offline learning systems that used Schoology in their lecture activities. This type of research is quantitative description with a factor analysis involving 100 respondents who were given a questionnaire. The instrument of the study was close-ended questionnaire that refer to several indicators such as student technology literacy, student learning styles, lecturer roles, and features of Schoology. Then, the results of this study showed that there were five important factors about the use of Schoology in facilitating their learning activities both inside and outside the classroom.